The Vulnerability Level of Groundwater Quality Degradation in The Ecosystem of Sand Dune Landscape on the Southern Coast of Central Java and the Yogyakarta Special Region, Indonesia - Prabang Setyono (International Journal of Advances in Applied Sciences, 2014)
The sand dune ecosystem phenomenon in the research area has unique and interesting characters. It is  identified that there is an  increase in the construction of the environment in the use of sand dune ecosystem which influence the groundwater quality. Such phenomenon is the manifestation of the existence of spatial dynamics influencing the groundwater degradation vulnerability. This research is aimed at 1) predicting the level of groundwater quality degradation vulnerability based on the sand dune ecosystem spatial dynamics; 2) developing an environmental management model to continuously maintain the availability of groundwater. The research employed survey research and inductive mapping. The aspect of the study included an environmental study with hydromorphological and hydrogeological approach. Analysis and evaluation were based on the multiplication of weight and rate, and were done on landscape units resulting from the map overlay. The research result  indicates  that there are 4 (four) classes of groundwater degradation vulnerability out of the 5 (five) classes of vulnerability determined beforehand. Groundwater degradation vulnerability classes III and IV indicate  problems of disturbances in the groundwater supply system and domestic and agricultural waste pollution. In order to overcome the disturbances in the groundwater supply system, water infiltration well should be constructed, communal domestic water processing should be encouraged, and in order to reduce pollution from the use of agricultural fertilizers, the fertilizers should be blended with clay.